Hans Kargaard Thomsen, (red): Arkivarer skriver breve. En antologi 1882-1959. Studier og kilder bd. 6. (Rigsarkivet/G.E.C. Gad, 1989). 181s., 183 kr. - Chr. Manniche, Jens (Historie/Jyske Samlinger, 1991)
-